Porphyromonas gingivalis, neuroinflammation and Alzheimer’s disease (Nigerian Journal of Physiological Sciences, 2022)
The oral microbiota dysbiosis, as well as lifestyle, geographical location, drug consumption, and dietary habits, are involved in the incidence and progression of dementia, Mild Cognitive Impairment (MCI), and some diseases such as obesity, diabetes, cardiovascular disease, preterm birth, rheumatoid arthritis, cancer, inﬂammatory bowel disease, and neurodegenerative disease e.g., Parkinson’s Disease (PD) and Alzheimer’s Disease (AD). AD is the most common cause of neurodegenerative disorder in the elderly. Also, neuroinﬂammation is the most common cause of AD pathogenesis. This study investigated the possible relationship between Porphyromonas gingivalis (P. gingivalis) and Alzheimer’s Disease. This review is based on research studies indexed in Scopus, Science Direct, PubMed, and Google Scholar databases.  The oral microbiota comprised various microorganisms, such as fungi, archaea, and bacteria. Porphyromonas gingivalis (P. gingivalis) is one of the microorganisms, it stimulates host immune cells and releases cytokines, lysosomal enzymes, nitric oxide, and reactive oxygen species that lead to cell damage, apoptosis, and inflammation. Therefore, periodontal disease (PerioD) through systemic inflammation leads to some problems like the progression of MCI, production and aggregation of beta-amyloid (Aβ) and tau protein in the brain of the elderly population. In addition, some treatment methods could modulate the adverse effects of P. gingivalis like probiotic dietary supplements, maintaining personal hygiene, as well as gingipain inhibitors which modulate cytokines through blocked Aβ production, ApoE proteolysis, and reduced neuroinflammation. In addition, therapeutic compounds like COR388 and COR286, as gingipain inhibitors, prevent P. gingivalis colonization in the brain and have a beneficial action in some conditions like aspiration pneumonia, low birth rate, rheumatoid arthritis, PerioD and AD.